The evolved nest, oxytocin functioning, and prosocial development - Tarsha, Mary S.; Narvaez, Darcia (Frontiers in Psychology, 2023)
Prosociality, orientation to attuned, empathic relationships, is built from the ground up, through supportive care in early life that fosters healthy neurobiological structures that shape behavior. Numerous social and environmental factors within early life have been identified as critical variables influencing child physiological and psychological outcomes indicating a growing need to synthesize which factors are the most influential. To address this gap, we examined the influence of early life experiences according to the evolved developmental niche or evolved nest and its influence on child neurobiological and sociomoral outcomes, specifically, the oxytocinergic system and prosociality, respectively. To-date, this is the first review to utilize the evolved nest framework as an investigatory lens to probe connections between early life experience and child neurobiological and sociomoral outcomes. The evolved nest is comprised of characteristics over 30 million years old and is organized to meet a child’s basic needs as they mature. Converging evidence indicates that humanity’s evolved nest meets the needs of a rapidly developing brain, optimizing normal development. The evolved nest for young children includes soothing perinatal experiences, breastfeeding, positive touch, responsive care, multiple allomothers, self-directed play, social embeddedness, and nature immersion. We examined what is known about the effects of each evolved nest component on oxytocinergic functioning, a critical neurobiological building block for pro-sociomorality. We also examined the effects of the evolved nest on prosociality generally. We reviewed empirical studies from human and animal research, meta-analyses and theoretical articles. The review suggests that evolved nest components influence oxytocinergic functioning in parents and children and help form the foundations for prosociality. Future research and policy should consider the importance of the first years of life in programming the neuroendocrine system that undergirds wellbeing and prosociality. Complex, interaction effects among evolved nest components as well as among physiological and sociomoral processes need to be studied. The most sensible framework for examining what builds and enhances prosociality may be the millions-year-old evolved nest.